Public speaking: a case study of speech anxiety in l1 and l2 - Tan, Rachel Chin Keok (2008)
A lot of research has confirmed that speaking in class makes the most anxiety in second and foreign language classroom (Young 1990). It is particularly true for young and inexperienced speakers (Beatty 1988). In public speaking, â€œa speaker presents a relatively continuous message to a relatively large audience in a unique contextâ€? (Devito 2000) can be too threatening to our students.However, fear of public speaking has been considered normal for every speaker even in their native language. It is a characteristic which many people have. In America, the Bruskin Associates conducted a nationwide survey in 1971 and revealed that the number one fear of Americans is the fear of giving a public speech. Even the fear of death came in the third. This paper investigates the causes of anxiety of public speaking on L1 and L2 and hopes to bring some suggestions to the teaching and training of speech delivery. Two questionnaires are given. An interview is conducted. Three speeches were done. The findings suggest that â€œfriendlyâ€? and customized steps should be adopted. Self-introduction, show-andtell speech and storytelling can be good starters. Finally, the language features of storytelling in second language teaching are exhibited.